Fast evaluation of electric vehicle hosting capacity considering users’ willingness - Jiamin Ge; Yi Xiong; Liang Che; Muliang Cai; Ruixiang Fan (International Journal of Electrical Power & Energy Systems)
The increasing integration of electric vehicles (EVs) has brought attention to the issue of insufficient hosting capacity (HC) in distribution networks (DNs). To enhance the security and optimize the HC of DNs, it is essential to accurately and quickly evaluate EV HC. Traditional methods fail to incorporate EV users’ willingness (UW) and have a large computational burden, leading to inaccurate and time-consuming evaluations. To address these issues, this paper proposes a feasible region (FR)-based EV HC evaluation strategy incorporating UW. Firstly, the EV-related FR of the DN is constructed based on the cutting plane method to accelerate evaluation. Then, EV user types are established by fully considering users’ differences and inter-type and intra-type UWs are quantified. Finally, based on quantified UW, FR-based EV HC evaluation is performed by charging scenario generation. Simulations on the modified IEEE 33-bus system verify that the proposed strategy ensures evaluation accuracy under UW while significantly accelerating the evaluation.